A conceptual framework for contemporary professional foot care practice: ‘’The value based digital foot care framework’’ - Kevin Deschamps; Antoine Brabants; Chris Nester; Gabriel Gijon‐Nogueron; Engin Simşek; Veronica Newton (Journal of Foot and Ankle Research, 2021)
Abstract Background A small minority of countries around the globe have podiatry as a recognized profession, hence, there are considerable differences among these countries when it comes to the curricula, the duration of training and legislation regulating the profession. The growth in research led evidence based practice, and the emerging digital landscape of health care practice, occur alongside trends in disease and health behaviours that strongly impact on foot health. As such, the changing complex role of the podiatrist requires critical reflection on current frameworks of practice and whether they are fit for purpose. This commentary presents a conceptual framework which sets the scene for further development of concepts in a podiatry context, reflecting contemporary health care beliefs and the changing expectations of health care and society. The proposed conceptual framework for podiatry practice utilizes the metaphor of an electronic circuit to reflect the vast and complex interconnections between factors that affect practice and professional behaviours. The framework helps in portraying and defining drivers of practice, actual practice as well potential barriers for current and future practice. The circuit emphasis the interconnectedness/interaction of three clusters: 1) internal factors, 2) interaction factors, 3) external factors. Conclusion Whatever promise this new framework holds, it will only be realised through conscious development of community consensus, respectful dialogue, constructive critical appraisal, and maintaining passion and focus on improving the health of people with foot related problems.